PO 18069 - Management of soft-tissue injuries in lower extremity fractures: literature review - da Rocha Macedo, Rafael; Gonçalves dos Santos, João Paulo; Putini, Dario; Miller Reis Rodrigues, Luciano (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Patients with lower extremity fractures have a high incidence of peri- and postoperative complications, such as extensive swelling, blisters, surgical wound infection, slow wound healing, persistent wound drainage and suture dehiscence. In calcaneal and tibial plafond fractures and ankle fractures/dislocations, especially in patients older than 50 years and those with diabetes, these complications are associated with a longer hospital stay and increased treatment costs and morbidity and mortality rates. The objective of this study is to perform a literature review of the management of blisters in lower extremity fractures and, based on the findings, to develop a management protocol for these lesions. Methods: Literature review of the state of the art in international databases. Articles published in indexed journals from 1995 to 2014 addressing soft-tissue management in ankle, calcaneal and tibial plafond fractures were selected. Results: Various treatment methods have been described in the literature: observation without intervention, application of sterile dressing, content aspiration, removal of the blister roof and application of an antibiotic ointment or topical treatment alone; all have similar outcomes regarding the delay in definitive surgery and the incidence of mild and severe soft-tissue complications. No large studies comparing these treatment alternatives are available. Conclusion: There is no consensus in the literature on the proper management of blisters. Further studies should be performed to define a protocol for the management of these lesions.